Optimization of Sariwangi Village Office Layout as a Catalyst for Comfort and Work Productivity - Azizah, Audini Nur; Wafiqoh, Haifa Nurul Aini; Chaniago, Harmon (Asosiasi Ahli Administrasi Indonesia, 2025)
This study analyzes the impact of office layout on employee comfort and productivity at the Sariwangi Village Office. Using a qualitative approach, this study evaluates aspects of lighting, color, air, and sound that affect work efficiency. The results show that a closed layout supports privacy and information security, but has challenges in the form of uneven lighting and noise from the surrounding environment. Air circulation in the office is quite optimal thanks to natural ventilation, while the blue color on the walls provides a calming psychological effect for employees. In addition, the minimal lighting aspect in some rooms causes reduced focus and accuracy of employees in working. High noise from traffic around the office also becomes an obstacle in maintaining concentration. This study emphasizes the importance of implementing ergonomic principles and optimal spatial planning to improve employee productivity. As a solution, the study recommends modifying the window layout with cross-ventilation techniques, utilizing indoor green plants to improve air quality, and using soundproofing to create a more conducive work environment. With the implementation of these solutions, the office is expected to become a more comfortable workplace, support employee efficiency, and contribute to increasing overall productivity.